Hak dan Perlindungan Konsumen pada Produk Asuransi Jiwa : Perspektif Regulasi dan Praktik di Indonesia - Oktavia Adi Roesnia; Tsabita Az Zahra; Arsya Ghaniyyah Hariyadi; Perwita Chandra Puspa; Berliana Clara Bella (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research examines life insurance consumer rights and protection in Indonesia, given the growth of the industry and the complexity of insurance products. The background of the research highlights the gap between regulation and consumer protection practices. The research objective is to analyze the effectiveness of regulations and their implementation. The research method used is normative-empirical juridical, with analysis of laws and regulations and case studies. The research findings show that although the regulations are comprehensive (Law No. 8/1999, Law No. 40/2014, POJK), their implementation still faces obstacles, such as lack of information transparency, harmful standard clauses, and suboptimal supervision. The implication of this research is the need to strengthen regulations, consumer education, and increase the effectiveness of dispute resolution mechanisms to increase consumer confidence in the life insurance industry.